Nuevos ámbitos de victimización: sobre el metaverso como lugar de comisión del delito = New fields of victimisation : on the Metaverse as a place of crime commission - Palma Herrera, José Manuel (Revista de victimología, 2025)
The metaverse, a virtual reality simulating physical experiences, transforms social and economic interactions. It allows for diverse activities and the acquisition of virtual goods using cryptocurrencies, which poses challenges for criminal law. Although similar crimes to those in the physical world—such as fraud or harassment— can be committed within the metaverse, its immersive nature amplifies the impact on victims of these experiences. This work examines whether the metaverse may be considered a place of commission of the offense for the purposes of applying Spanish criminal law. Our Supreme Court has recognized social networks like YouTube as a place of commission of the offense for punitive purposes, but this precedent does not necessarily entail the application of criminal law to the metaverse as a virtual territory equivalent to Spanish physical territory. The application of criminal law in the metaverse should be guided by the principles of territoriality and ubiquity used for crimes committed via the internet. This would mean that Spanish law would apply if the offender performs all or part of the typical conduct in Spain, or if the result occurs wholly or partially within Spanish territory. Beyond this conclusion, it does not appear likely that the metaverse could eventually be considered a territory under state sovereignty, and consequently, a true place of commission of the offense.